2014
DOI: 10.1007/s11214-014-0078-y
|View full text |Cite
|
Sign up to set email alerts
|

Theory and Modeling for the Magnetospheric Multiscale Mission

Abstract: The Magnetospheric Multiscale (MMS) mission will provide measurement capabilities, which will exceed those of earlier and even contemporary missions by orders of magnitude. MMS will, for the first time, be able to measure directly and with sufficient resolution key features of the magnetic reconnection process, down to the critical electron scales, which need to be resolved to understand how reconnection works. Owing to the com- plexity and extremely high spatial resolution required, no prior measurements exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 276 publications
(282 reference statements)
1
44
0
Order By: Relevance
“…withb the magnetic field unit vector, the sheath/sphere subscripts denoting z =∞, −∞, respectively. These asymmetries show positive similarities with certain magnetopause properties, given typical magnetopause conditions [e.g., see Burch et al, 2016;Hesse et al, 2016]. We stress that these asymmetries relate to a particular selection of parameters, which are chosen to demonstrate an example of the types of asymmetric conditions that the distribution function (DF) can support.…”
Section: The Current Sheet Equilibriummentioning
confidence: 96%
“…withb the magnetic field unit vector, the sheath/sphere subscripts denoting z =∞, −∞, respectively. These asymmetries show positive similarities with certain magnetopause properties, given typical magnetopause conditions [e.g., see Burch et al, 2016;Hesse et al, 2016]. We stress that these asymmetries relate to a particular selection of parameters, which are chosen to demonstrate an example of the types of asymmetric conditions that the distribution function (DF) can support.…”
Section: The Current Sheet Equilibriummentioning
confidence: 96%
“…Tensor (E = −∇ · ↔ P /en) The expected role of a divergence of the electron pressure tensor and the associated electron nongyrotropy in electron demagnetization leading to magnetic reconnection is discussed by Hesse et al (2014). Henderson et al (2006) have reported measurements of electron pressure tensor gradients using the four Cluster spacecraft.…”
Section: Divergence Of Electron Pressurementioning
confidence: 99%
“…MMS includes a comprehensive theory and modeling team that has provided the inputs required for an optimum experiment (Hesse et al 2014). As described in the Appendix, the SMART team is significantly augmented by the addition of three Interdisciplinary Scientist Teams (Goldstein et al 2015;Phan et al 2014;Goldman et al 2015), which have provided important inputs by virtue of MHD and kinetic modeling and experience with previous multi-spacecraft magnetospheric missions (Cluster and THEMIS).…”
Section: Mission Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MMS science objectives and requirements are discussed in companion articles (Burch et al 2014, this issue;Torbert et al 2014, this issue;Hesse et al 2014, this issue), so we only provide a brief summary specific to the ADP and DSP.…”
Section: Science Objectives and Requirementsmentioning
confidence: 99%